Information technology. International Standardized Profiles FVT1nn. Virtual Terminal Basic Class. Register of VTE-profiles. FVT121, FVT122. S-mode forms and paged VTE-profiles Part 1, (15th March 1997) - British Standards Institution,
No abstract available